2013
DOI: 10.9775/kvfd.2012.7620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan on Glycerol-induced Myoglobinuric Acute Renal Failure in Rats

Abstract: SummaryMyoglobinuric acute renal failure (mARF) is an uremic syndrome which develops due to damage of skeletal muscle. It was demonstrated that free radicals and nitric oxide (NO) play an important role in pathogenesis of mARF. Our aim was to investigate the effect of losartan, a drug known for its antioxidant effect, on mARF. In our study, a total of 34 male Spraque Dawley rats were divided into four groups. 1 st and 2 nd groups were injected with saline, 3 rd and 4 th groups were injected with intramuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
(45 reference statements)
3
3
1
Order By: Relevance
“…In accordance with our results, Singh et al and Kaya et al, reported an increase in blood urea and creatinine levels in ARF [23,24]. Also the GFR was found to be decreased [25,26].…”
Section: Tablesupporting
confidence: 95%
See 4 more Smart Citations
“…In accordance with our results, Singh et al and Kaya et al, reported an increase in blood urea and creatinine levels in ARF [23,24]. Also the GFR was found to be decreased [25,26].…”
Section: Tablesupporting
confidence: 95%
“…This was in accordance with studies conducted by Chander et al [37] and Aydogdu et al [6]. However, no significant decrease in GSH level was noted by Kaya et al studying on the same animal model [24]. GSH acts as a radical scavenger by itself, and as a detoxicant by eliminating different electrophilic toxic compounds [38].…”
Section: Oxidative Stresssupporting
confidence: 86%
See 3 more Smart Citations